Anxiety, fears and fear-avoidance beliefs and therapeutic outcome after lumbar microdiscectomy - Slobodan Pantelinac; Dušica Simić-Panić; Gordana Devečerski; Snežana Tomašević Todorović (Acta Clinica Croatica)
Microdiscectomy is one of the surgical methods for the treatment of herniated intervertebral disc in patients with low back pain. The aim of the research was to evaluate the presence of psychological and cognitive-behavioral factors, including anxiety, fears and fear-avoidance beliefs of physical activity and work and their correlation with the pain and functional disability in patients after lumbar microdiscectomy and subsequent physical therapy. Th e research was performed on 198 patients (95 men and 103 women), mean age 50.20±10.26 years. Th e following questionnaires were used in the study: Spielberger Anxiety Inventory-State and Trait; Fear-Avoidance Beliefs Questionnaire (Physical activity and Work); for intensity of pain, visual analog scale and Oswestry Low Back Pain Disability Questionnaire. Th ese assessments were carried out after microdiscectomy, as follows: just before rehabilitation treatment, and 1, 3 and 6 months after microdiscectomy. Th e pain and functional disability had significant correlations with the following factors: anxiety-state (p<0.01), anxiety-trait (p<0.01), fear/avoidance beliefs - physical activity (p<0.01) and fear/avoidance beliefs - work (p<0.01). Th e pain and functional disability in patients after lumbar microdiscectomy showed significant correlation with anxiety, fears and fear-avoidance beliefs. The mentioned psychological and cognitive-behavioral factors can predict the degree of functional recovery and indicate additional therapy after lumbar microdiscectomy.